Enhancing Oral Health Care Access for School Children: A Perspective. (Nigerian Dental Journal, 2024)
Inadequate access to oral health services for school children remains a pervasive issue in Nigeria. According to a study, a mere 20% of enrolled students have availed themselves of dental visits following referrals from dentists. Various barriers, such as geographical location, socioeconomic status, lack of awareness about the importance of oral health, and fear of treatment, contribute to this low utilization rate. The resulting problem exacerbates social class disparities within the country. To address this pressing concern, we conducted an exhaustive academic review encompassing peer-reviewed literature, policy documents, and other relevant materials. This review underscored three potential policy alternatives: bolstering educational campaigns on oral health, implementing mobile dental clinics, and establishing on-site school-based dental clinics—an innovative approach in the Nigerian context. Additionally, we will delve into insights from a successful case study of a model on-site school oral healthcare clinic in Ile-Ife. Recognizing that each approach comes with its own set of advantages and disadvantages, we propose a concise School Oral Health Policy. This policy aims to establish a framework for incorporating these remedies efficiently, providing a comprehensive solution to the issue of insufficient availability of dental healthcare services among Nigerian school pupils.
Keywords: Oral Health Education, Diet, Hygiene, Dental Clinic Attendance, Folktales, Pupils